(untitled) (Research, Society and Development, 2022)
Pregabalin is a drug commonly used in psychiatry, neurology, and primary health care. It is an anticonvulsant widely used in the treatment of epilepsy, anxiety, fibromyalgia and neuropathic pain. It works by binding to voltage-gated calcium channels, exerting analgesic and anxiolytic activity. It has GABA-like properties and is involved in the dopaminergic reward system. The objective of this systematic review was to describe the status of current knowledge in relation to the topic, highlighting possible paths for future research, guiding other researchers and directing new publications with objectives correlated to the current diagnosis. In the present systematic review, we used original and comprehensive, open access scientific research, carried out between 2016 and 2021, related to the drug Pregabalin, highlighting its relationship with the testes and the Endocrine System in male rats. In order to map the scientific production, an exploratory-descriptive research was carried out, through a systematic analysis. The main collection of the Web of Science (Clarivate Analytics) was used as a search base. Studies have shown that pregabalin affects FSH, LH and testosterone levels, causing changes in spermatogenesis. Pregabalin causes significant changes in hormone levels, negatively impacting the production of healthy sperm. Psychotropic drugs, particularly pregabalin, can also reduce sperm quality, decreasing patients fertility potential.